Antibacterial Effect of Cinnamomum zeylanicum and Curcuma longa Extracts and their Synergistic Effect with Antibiotic Sulfamethoxazole - Dawood, Noor J. (International Journal of Pharmaceutical & Biological Archive, 2022)
Study focused on evaluation of antibacterial effect of Cinnamomum zeylanicum and Curcuma longa extracts and their synergistic effect with antibiotic Sulfamethoxazole. Antimicrobial activity of plant extracts against Escherichia coli. C. longa was showed the highest effect against E. coli with a zone of inhibition 13 and 14.5 mm.at a concentration of 100 and 200 mg/mL, respectively. Antimicrobial activity was observed by C. zeylanicum, with a zone of inhibition 9 and 13.9 mm at a concentration of 100 and 200 mg/mL, respectively. C. longa was showed the highest effect against Staphylococcus aureus with a zone of inhibition 11 and 16.8 mm at a concentration of 100 and 200 mg/mL, respectively. No antimicrobial activity was observed by C. zeylanicum, at a concentration of 100 mg/mL and a zone of inhibition 10 mm at a concentration of 200 mg/mL, antibiotic activity of Sulfamethoxazole (50 mg and 100 mg) against S. aureus and E. coli activity was observed by Sulfamethoxazole, which showed the strongest activity against S. aureus and E. coli with a zone of inhibition 17 and 18.5 mm at a concentration of 50 mg, respectively. While was zone of inhibition using Sulfamethoxazole (100 mg )19.2 and 21 mm. against S. aureus and E. coli. respectively. We evaluated in vitro synergism between extracts of Cinnamomum Zeylanicum and Curcuma longa extracts and antimicrobial drugs utilized against S. aureus and E.coli using well diffusion method, was C. zeylanicum extract has the best synergistic effect on E. coli when added on Sulfamethoxazole. As for Sulfamethoxazole, it has been the highest effect on bacteria when add C. zeylanicum extract (20 mm) and also when add C. longa extract (21 mm). C. zeylanicum extract has the best synergistic effect on S. aureus when added on Sulfamethoxazole. As for Sulfamethoxazole, it has been the highest effect on bacteria when add C. zeylanicum extract (19.6 mm) and also when add C. longa extract (21.2 mm).